An investigation on wear characteristics of additive manufacturing materials. (2021) - Kumar, Aditya; Choudhary, Abhishek; Tiwari, Abhishek; James, Christopher; Kumar, Harish; Kumar Arora, Pawan; Akhtar Khan, Shahroz
Abstract: Wear, heat and friction generate problems in working mechanisms of a machine because of the high and repeated use of machines. A huge cost on machines would be saved if the wear rate on machines is taken into consideration as wear reduces lifespan of material. Every mechanism on a machine has a surface which is in relative motion with another part of the machine (e.g., sliding, rolling etc). The main focus is to control the high wear rate of a material. The characteristics of the different materials differ due to their quantum differences. The present work is an investigation covering wear characteristics of additively printed specimen with materials like steel, nickel, aluminium, acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), etc. The availability of a variety of wear testing methods helps to conduct the detailed research of microstructure and composition of touching surfaces. The recent work on wear not only helps to understand the mechanism of contact and rigorousness transfer during sliding but also helps in better understanding of properties like critical angle for maximum wear rate by particle.